2020
DOI: 10.1051/e3sconf/202021018058
|View full text |Cite
|
Sign up to set email alerts
|

The challenge and opportunities of thailand education due to the covid-19 pandemic: case study of Nakhon Pathom, Thailand

Abstract: This research aims to define the challenges and opportunities and how educational staff, teacher, lecturer in Nakhon Pathom, and Thailand respond to the disruptive impact of the COVID-19 pandemic, and understand the education obstacles due to the Covid19 pandemic in Nakhon Pathom, Thailand. The information was collected by in-depth interview with 28 experienced educational staff in Nakhon Pathom, Thailand, using snowball sampling during April 2020. Scope of information on the education obstacles, the challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…According to the existing methods in several applications of data analytics in the Thailand education sector, it found that most of the research relied heavily on data collection, questionnaires, and surveys combined with statistical processes [25][26][27][28][29], while other academic works preferred different methods, such as classification [24] and snowball sampling [30]. Even if statistical methods provided satisfactory effectiveness for data analysis in different situations where the size is not very large [44], massive data volumes induced by the economic conditions during the COVID-19 outbreak have affected the accuracy of data assessment and analytics, whether it is a study plan [37][38][39][40] or an employment projection after each academic year [43].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the existing methods in several applications of data analytics in the Thailand education sector, it found that most of the research relied heavily on data collection, questionnaires, and surveys combined with statistical processes [25][26][27][28][29], while other academic works preferred different methods, such as classification [24] and snowball sampling [30]. Even if statistical methods provided satisfactory effectiveness for data analysis in different situations where the size is not very large [44], massive data volumes induced by the economic conditions during the COVID-19 outbreak have affected the accuracy of data assessment and analytics, whether it is a study plan [37][38][39][40] or an employment projection after each academic year [43].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Although a survey of students, teachers, and industry professionals, requires further prevail in Thailand Automation 4.0, an appropriate direction through descriptive analysis along with possible teaching styles can attract new applications in the future. Meanwhile, defining challenges and opportunities through Snowball Sampling is how educators or teachers in Nakhon Pathom, Thailand, reflect the impact of the COVID-19 outbreak [30]. The data were collected through in-depth interviews and interpreted along with the causeand-effect analysis to determine the challenges and opportunities of 28 experienced educational respondents.…”
Section: Data Analytics Influences In Thailand Education Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few teachers were trained to use technology and to teach online. Hence, online teaching became a hurdle to most teachers, especially in rural areas (Kenan Foundation, 2023;Vanpetch & Sattayathamrongthian, 2020). According to Suksawas and Yiemkuntitavorn (2022), teachers need more training in the essential functions of online learning modes, and they lack technical support, e.g.…”
Section: Health Sector Education Sectormentioning
confidence: 99%
“…Education in Thailand faces several challenges due to the many institutions that limit face-to-face learning and training with social distancing policies that require the learning process to shift to virtual classrooms [20]. Many schools are located in rural areas and have low incomes.…”
Section: Thailandmentioning
confidence: 99%